2008
DOI: 10.1016/j.ydbio.2008.05.528
|View full text |Cite
|
Sign up to set email alerts
|

Indian hedgehog signaling from endothelial cells is required for sclera and retinal pigment epithelium development in the mouse eye

Abstract: The development of extraocular orbital structures, in particular the choroid and sclera, is regulated by a complex series of interactions between neuroectoderm, neural crest and mesoderm derivatives, although in many instances the signals that mediate these interactions are not known. In this study we have investigated the function of Indian hedgehog (Ihh) in the developing mammalian eye. We show that Ihh is expressed in a population of non-pigmented cells located in the developing choroid adjacent to the RPE.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 80 publications
3
48
0
Order By: Relevance
“…However, some previous studies are consistent with our finding that Ihh levels influence ocular development. For example, overexpression of murine Ihh in zebrafish embryos caused expansion of pax2 expression in the optic stalk (Hammerschmidt et al, 1996), and in the mouse, Ihh was shown to be required for proper development of the RPE and peri-ocular tissues (Dakubo et al, 2008). Interestingly, although we observed a significant elevation (approximately 4-fold) of ihhb expression at 8-12 hpf in sox4 morphants, this increase was even more pronounced at 18 and 24 hpf (approximately 15-fold).…”
Section: Discussionmentioning
confidence: 99%
“…However, some previous studies are consistent with our finding that Ihh levels influence ocular development. For example, overexpression of murine Ihh in zebrafish embryos caused expansion of pax2 expression in the optic stalk (Hammerschmidt et al, 1996), and in the mouse, Ihh was shown to be required for proper development of the RPE and peri-ocular tissues (Dakubo et al, 2008). Interestingly, although we observed a significant elevation (approximately 4-fold) of ihhb expression at 8-12 hpf in sox4 morphants, this increase was even more pronounced at 18 and 24 hpf (approximately 15-fold).…”
Section: Discussionmentioning
confidence: 99%
“…We observed a substantial reduction in the expression of Ihh [which is expressed in choroid (Dakubo et al, 2008)] at P0.5 (5.2-fold) and P6.5 (3.3-fold), Ptch2 (2.2-times less at P0.5 and 2.3-times less at P6.5), Wnt3a (1.5-times less at P6.5) and Sfrp5 (2-times less at P0.5). The expression of two Notch pathway genes, Hes1 and Dll1, was also more than halved at P0.5 and P6.5, whereas Fzd5 expression was increased by 2.3-fold at P0.5.…”
Section: Altered Expression Of Selected Signaling Genes In Mutant Rpementioning
confidence: 92%
“…Eye development not only depends on SHH, but also on the related morphogen indian hedgehog (IHH) produced by the choroid adjacent to the RPE (Dakubo et al, 2008). Expression of Ihh in the choroid was unchanged in Lrp2 À/À mice (Figure S3B).…”
Section: Lrp2 Deficiency Causes Ectopic Induction Of Shh Signals In Tmentioning
confidence: 99%